DIAGNOSTIC EFFECTIVENESS OF THE IMPROVED METHOD OF LABORATORY DIAGNOSTICS OF GOAT DIGESTIVE ORGANS’ STRONGYLATOSES - Prima, O. B. (Scientific Progress & Innovations, 2021)
The diagnostics of animal parasitic diseases has its own peculiarities, and is also a key link in the system of measures aimed at combating and preventing invasive diseases. Live-time laboratory diagnostics of strongylatoses of ruminants’ digestive organs is based on the use of coproovoscopic flotation methods, the efficacy of which varies. The aim of the paper was to study the diagnostic effectiveness of an advanced meth-od of coproovoscopy in case of strongylatoses of goats’ digestive organs. The research was performed in the Laboratory of the Department of Parasitology and Ichthyopathology of Stepan Gzhytskyi National Universi-ty of Veterinary Medicine and Biotechnologies of Lviv. The comparison of the diagnostic effectiveness of coproovoscopic flotation methods of life-time laboratory diagnostics of goats’ digestive tract strongylatoses was conducted. The advanced method for diagnosing strongylatoses of goats’ gastrointestinal tract has been proposed. According to the results of the studies, it was found that regardless of the exposure of fecal sus-pension, the most effective in terms of invasion intensity (for fluctuations from 311.76 to 532.50 eggs/g) was the proposed method for diagnosing strongylatoses of goats’ digestive organs. At fecal suspensionexposure for 5 min, the improved method was more effective than the methods of Kotelnykov-Khrenov by 35.85 %, Mallori – by 21.95 %, Melnychuk – by 20.75 %. At this exposure, out of 20 diseased animals, 17 samples were found to be positive by the improved method and the Melnychuk’s method, 13 samples were positive by the Kotelnykov-Khrenov’s method, and 15 samples – by the Mallori’s method. At an exposure of 10 min, the intensity of strongylatosis invasion during the application of the improved method made 352.78 eggs/g, which exceeded the values obtained using the methods of Kotelnykov-Khrenov (by 28.19 %), Mallori (by 20.79 %), Melnychuk (by 19.69 %). The number of detected positive samples established by these methods was 18, 15, 17 and 18, respectively. At an exposure of 15 min, the diagnostic effectiveness of the developed method exceeded the generally-known methods of coproovoscopy by 22.91–33.17 %. The highest number of positive samples was found when using the advanced method. The obtained data confirm the high diagnostic efficiency of the proposed combined flotation liquid as a method of coproovoscopy for strongylatoses of goats’ digestive organs.